Just ask! : be different, be brave, be you - Sotomayor, Sonia, 1954- (Philomel Books, 2019)
In this creative non-fiction story, Sonia and her friends plant a garden, and each one contributes in his or her own special way, in a book that celebrates the many differences among humans. In this warm and inclusive story by U.S. Supreme Justice Sonia Sotomayor, inspired by her own childhood diagnosis of diabetes, readers join along as differently abled kids use their strengths to work together and learn about each other.